Effect of Different Baits on Catch of Mangrove Crab - Alwin Muhamad; Abd Hafidz Olii; Alfi Sahri Baruadi (The NIKe Journal, 2018)
This study aims to determine the effect of different kinds of bait on the catch of mangrove crab (Scylla serrata) in Kwandang District, North Gorontalo Regency. This research was conducted in September 2015 - August 2016. The research method of exferimental fishing was carried out with 3 treatments, namely selar fish bait, chicken head bait and golden snail bait. Experimental data were analyzed by randomized block design (RBD) and Duncan's test. The results showed that different types of bait affect the catch. Chicken head bait is the best bait that gives more catches than the other baits. Duncan's multiple range test results showed that the treatment of chicken head bait was significantly different from the treatment of goldfish and golden snails. Furthermore, the treatment of selar fish bait was significantly different from the treatment of golden snail bait. Keywords: bait; mangrove crab; Scylla serrata; catch.